Presenting an Advanced Model of Women’s Entrepreneurship Using Fuzzy Analytic Hierarchy Process - Ansari Amoli, Parisa; Gholipour kanani, Yousef; Bagherzadeh , Mohammadreza; Tabari , Mojtaba (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this research is to identify and prioritize the factors affecting women’s entrepreneurship. Methodology: This study is applied in aim and descriptive in method. To determine the weight of criteria and sub-criteria for this issue, the Fuzzy Analytic Hierarchy Process (FAHP) was utilized. Accordingly, after identifying the criteria and sub-criteria for each, a questionnaire was designed to match them and distributed to experts. In the current issue, the effects of criteria affecting women’s entrepreneurship were examined with 20 decision-makers. In the next step, the questionnaires filled out by experts were transferred to Excel software. Findings: The factors affecting women’s entrepreneurship include five criteria consisting of family, personality, economic, social, and cultural criteria. The family criterion has eight sub-criteria, the personality criterion has ten sub-criteria, the economic criterion has seven sub-criteria, and the social and cultural criteria each have five sub-criteria. The results show that among the criteria, the "personality" criterion, with a weight of 0.3071, and the "cultural" criterion, with a weight of 0.1103, ranked first and last, respectively. In addition, the "economic" criteria with a weight of 0.2011, "family" with a weight of 0.1931, and "social" with a weight of 0.1884, are ranked second to fourth, respectively. Moreover, among the thirty-five sub-criteria, the sub-criteria of "extensive social relationships" with a weight of 0.0530, "job satisfaction" with a weight of 0.0462, "institutions and resources" with a weight of 0.0448, "determination and will" with a weight of 0.0444, and "guidance and leadership" with a weight of 0.0428, are ranked first to fifth, respectively. Also, the sub-criteria of "market access" with a weight of 0.0270, "role models" with a weight of 0.0165, "transportation system" with a weight of 0.0165, "role conflict" with a weight of 0.0135, and "marital status" with a weight of 0.0088, respectively rank thirty-first to last. Conclusion: The research underscores a strong correlation between personality traits and women’s entrepreneurship, pointing to the necessity of tailored programs in higher education to foster entrepreneurial inclinations.